Decomposing deviations of scanned surfaces of sheet metal assemblies. (October 2021) - Claus, Felix; Hamann, Bernd; Leitte, Heike; Hagen, Hans
Graphical abstract: Highlights: Method for identifying and visualizing errors in sheet metal assemblies caused by wrong positioning of attachment points. Decomposition of displacement fields, obtained from 3D-scanned post-assembly shapes, into portions contributed by each mechanical boundary constraining the part. Improvement of decision making in quality assurances of exterior assemblies. Abstract: We present a finite-element-based approach to support quality assurance for assembly processes of non-rigid sheet metal parts in the automotive and aerospace industries. These parts have adjustable mechanical boundaries, making it possible to compensate geometrical deviations caused by the production process of components. Every part produced must be adjusted individually. Determining what boundaries to adjust to and in what direction is challenging and requires experience. Our goal was to identify sources of measured surface deviations after part assembly and provide valuable information to the quality assurance engineer. We solve the corresponding parameter estimation problem via a least-squares approach. From the estimated parameter states that led to measured deviations, additional visualizations are calculated to support the inspection engineer when deriving countermeasures.